2019
DOI: 10.5688/ajpe6764
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Unmet Patient Care Needs Through Curricular Development of Student Pharmacist Leadership and Entrepreneurial Skills

Abstract: Objective. To develop, deliver, and evaluate an innovative curriculum, designed to increase student pharmacists' skills and confidence in addressing unmet patient care needs and the Institute for Healthcare Improvement (IHI) Triple Aim goals in the community pharmacy setting. Methods. Course modules developed collaboratively between the University of Washington andWashington State University focused on student pharmacist exposure to and direct application of leadership theory in addressing real world challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It allowed to highlight the main leadership development competencies (Junk et al 2013(Junk et al , 2016 [1,6], as well as to study their importance for students on the basis of Delphi method, a survey of students and a systematic review of the related literature (Feller et al, 2016and Tucci et al, 2017, Reed et al, 2019 [7,8,9]. The description of leadership development opportunities in the USA, as a rule, of courses and projects, the research of students' preferences regarding their content (Panther et al, 2017, Feller et al, 2016, Sucher et al, 2013, Patterson et al, 2013) might lead to the formation of key priorities on leadership issues for pharmacy students [7,10,11,12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It allowed to highlight the main leadership development competencies (Junk et al 2013(Junk et al , 2016 [1,6], as well as to study their importance for students on the basis of Delphi method, a survey of students and a systematic review of the related literature (Feller et al, 2016and Tucci et al, 2017, Reed et al, 2019 [7,8,9]. The description of leadership development opportunities in the USA, as a rule, of courses and projects, the research of students' preferences regarding their content (Panther et al, 2017, Feller et al, 2016, Sucher et al, 2013, Patterson et al, 2013) might lead to the formation of key priorities on leadership issues for pharmacy students [7,10,11,12].…”
Section: Methodsmentioning
confidence: 99%
“…According to the survey results, more than 90% of students who passed through this elective course, 'strongly agree' that "this course helped me learn more about aspects of my character that are essential for leaders". Leadership development opportunities at The University of Iowa College of Pharmacy, (Patterson et al, 2013) [12], at University of Washington и Washington State University College of Pharmacy (Panther et al, 2017) also confirmed their effectiveness in "developing leadership skills in students and inspiring student pharmacists to be agents of change" [10].…”
Section: Leadership Development Opportunities For Pharmacy Studentsmentioning
confidence: 98%
“…"innovation", "medical education", "leadership", "qualitative research", "healthcare innovation", "design thinking" and "technology transfer"that reflect healthcare entrepreneurship research pertaining to innovation and leadership. Studies in cluster emphasize the importance of developing entrepreneurial skills and innovation (Panther et al, 2019;Sharma et al, 2022a), which could be done through design thinking (Niccum et al, 2017). They also highlight the returns of entrepreneurial leadership in fostering innovation behavior among medical personnel such as nurses (Bagheri and Akbari, 2018), as well as the that relating to innovation spin-offs such as technology transfer (Helm et al, 2010).…”
Section: Major Themes and Topics In Healthcare Entrepreneurship Resea...mentioning
confidence: 99%